THE TRACE OF POSTMODERN FEATURES IN DAVID MAMET'S AMERICAN BUFFALO - Wahad Kalil Hashem (PT. Antis International Publisher, 2024)
The present research intends to study the multifarious interface of postmodern features and power relations in David Mamet's distinguished drama, American Buffalo, in light of Michel Foucault's theory of power. This investigation seeks to find the discreet hints of postmodern aesthetics ingrained in the storyline of the play, and simultaneously scrutinize how Foucault's theory of power brightens the plentiful accounts of power relations, intervention, and confrontation amid the characters. Taking advantage of Foucault's theories of power as an omnipresent force that works through discourses, associations, and communal dealings, this paper scrutinizes the way in which Mamet's employment of such postmodern components as disjointed descriptions and verbal play interweaves with and impedes the power relations in the world of American Buffalo. By positioning the characters in a mesh of power dealings that regulate their movements, stimulations, and identities, this exploration analyzes the central power skirmishes that drive the melodramatic pressures in the play. As well, the contemplation of ethical predicaments resulting from the power subtleties signified in American Buffalo delivers important considerations of issues of reconnaissance, supremacy, and confrontation.